Beyond the Role: A Body-Based Approach to Acting, Imagination, and Inner Motives in Actor Training: Melampaui Peran: Pendekatan Keaktoran Berbasis Tubuh, Imajinasi, dan Motif Batin dalam Pelatihan Aktor - Dharma, Budi; Sutardi, Edi (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
this study examines the Melbeyond the Role ("Beyond the Role") acting method, a training approach that emphasizes honesty of expression, bodily awareness, and internal reflection. Developed through intensive workshop practice, this method positions the body, breath, and imagination as the foundation of performance creation, offering an alternative to acting practices that rely heavily on textual repetition and external imitation. The research applies a practice-based research approach, with data gathered from direct observation, reflective notes, and workshop documentation. A descriptive-reflective analysis was conducted to identify the core principles, training stages, and pedagogical mechanisms of the method. The findings indicate that Melampaui Peran integrates the body, imagination, and inner motive as the primary components of authentic performance. The body functions as a site of knowledge and awareness, imagination provides emotional context grounded in realistic presence, and inner motive directs the logic behind every performed action. The interplay of these elements produces a form of honest expression that enables transformative experiences for the actor on stage. Conceptually, the method extends classical acting theories (Stanislavski, Meisner, Grotowski) by grounding them in reflective and experiential processes shaped within the Indonesian performance context. This study contributes to the development of actor training pedagogy in drama, dance, and music education programs in Indonesia.